Selenium Application in Improving Chicory (Cichorium intybus) Productivity and Quality - N. Umami; E. R. V. Rahayu; B. Suhartanto; A. Agus; M. M. Rahman (Tropical Animal Science Journal, 2022)
Selenium (Se) is an essential mineral element needed by livestock and human. The amount of Se intake is largely determined by the Se content in the plants (food and feed) consumed. This study aimed to analyze the effect of Se fertilizer on the morphological characters, biomass yield, nutrient content, and in vitro nutrient digestibility of Cichorium intybus. This study was conducted for four months, starting from May to August 2019, located at the Faculty of Animal Science, Universitas Gadjah Mada. The seeds of Cichorium intybus var. Chico was sown in 24 plots and the plots were arranged in a completely randomized block design. Three levels of Se fertilization treatments (0, 3.5, and 7.5 mg/m2) were applied with 8 replicates. Plant defoliation on every 45 days: namely the first defoliation (from sowing to 45 days), the second defoliation (regrowth 1 up to 45 days), and the third defoliation (regrowth 2 up to 45 days). In all studied parameters, the results showed that chicory with Se fertilizer (3.5 and 7.5 mg/m2) was higher (p<0.05) than chicory without Se fertilization. The chicory with Se fertilizer at the level of 7.5 mg/m2 had higher (p<0.05) leaf width, biomass yield, crude protein, and Se content, and in vitro nutrient digestibility (dry matter, organic matter, crude protein) compared to that with Se fertilizer at the level of 3.5 mg/m2. Chicory at the third defoliation had a higher biomass yield and Se content than at the second defoliation. In conclusion, the best combination from this study was the third defoliation, with Se fertilizer level of 7.5 mg/m2.